Development of novel biliary metal stent with coil-spring structure and its application in vivo swine biliary stricture model - Cho, In Rae; Lee, Sang Hyub; Choi, Jin Ho; Park, Namyoung; Lee, Min Woo; Kim, Joo Seong; Jeong, Seok; Lee, Don Haeng; Jeong, Tae-Won; Ki, Byoung-Yun; Paik, Woo Hyun; Ryu, Ji Kon; et al. (Frontiers in Oncology, 2023)
Background: As of date, endoscopic biliary stenting with plastic stent (PS) and self-expandable metal stent (SEMS) have been widely used for the palliation of biliary tract strictures. However, these two stents have several limitations regarding the management of biliary strictures caused by intrahepatic and hilar cholangiocarcinoma. PS has short patency and also risks bile duct injury and bowel perforation. SEMS is difficult to revise when occluded by tumor overgrowth. To compensate for such shortcomings, we developed a novel biliary metal stent with coil-spring structure. The aim of this study was to investigate the feasibility and efficacy of the novel stent in a swine model. Methods: The biliary stricture model was prepared in six mini-pigs using endobiliary radiofrequency ablation. Conventional PS (n=2) and novel stents (n=4) were deployed endoscopically. Technical success was defined as successful stent placement and clinical success was defined as >50% reduction of serum bilirubin level. Adverse events, stent migration, and endoscopic removability for one month after stenting were also assessed. Results: The biliary stricture was successfully created in all animals. The technical success rate was 100 % (6/6). In the novel stent group, the clinical success rate was 75% and the median pre- and post-treatment serum bilirubin levels were 3.94 and 0.3 mg/dL. Stent migration occurred in two mini-pigs of novel stent group and one PS and two novel stents were successfully removed by endoscopy. There was no stent-related mortality. Conclusions: The newly designed biliary metal stent was feasible and effective in a swine biliary stricture model. Further studies are needed to verify the usefulness of the novel stent in the management of biliary strictures.